A Primer on Policies for Jobs - Nallari, Raj (World Bank, 2012)
A primer on policies for jobs is based on materials and input provided during the labor market courses conducted during the past 10 years. Its objective is to provide government policy makers, researchers, and labor market practitioners and other specialists with a practical guide on how to strengthen labor market institutions, especially in light of the global financial crisis. This primer emphasizes six pillars of labor market institutions: global trends, job creation, labor market policies, education, entrepreneurship, and globalization. Chapter one addresses current labor market trends and job creation, particularly in tough conditions. Chapter two examines channels of job creation and ways to strengthen labor market institutions to ensure sustainable job growth, considering factors such as investment climate, job policy, industrial policy, social protection, and other labor market issues. Chapter three focuses on labor market policies in developing countries. Chapter four highlights the impact of education and skills on labor market outcome. Chapter five discusses entrepreneurship along three key dimensions: development and growth, job creation, and female entrepreneurship. Finally, chapter six addresses the relationship between jobs and globalization.